90.6k views
4 votes
Perform the indicated operation. 3 + (-4) 1 -1 7 -7

User Pfranza
by
6.2k points

2 Answers

4 votes

For this case, what we must do is solve the following algebraic expression:


3 + (-4)

According to the law of signs we have to:


+ * + = +\\+ * - = -\\- * - = +

Thus, applying the aforementioned law we have to:
3 + (-4) = 3-4

Rewriting we have:


3 + (-4) = -1\\

Answer:


3 + (-4) = -1\\

User Anjaneya
by
5.9k points
5 votes

Answer:

-1

Explanation:

3+-4

Since the signs are opposite, we subtract the two numbers and take the sign of the larger

4-3 =1

The sign of the larger number (-4) is negative

-1

3+-4 = -1

User Aviad Rozenhek
by
6.0k points